2015
DOI: 10.1039/c5qi00064e
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen activation by copper camphor complexes

Abstract: In situreduction of CuCl2enables formation of Cu(i) complexes prone to activate molecular oxygen from air towards catalytic oxidation of 1,3-dicarbonyls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…The mechanism of O 2 activation by Cu(II) could involve Cu(I), as reported elsewhere. 46 Regarding Co-catalysts, upon O 2 addition most Co(II) complexes form kinetically inert lowspin Co(III) terminal superoxide or μ-peroxide compounds that are active only in catalysis by addition of a coreductant (often, an organic ligand with redox properties). 47 Hanna et al reported the oxidation of DMPO to the DMPO/ • OH adduct by Co(II) and ethylenediamine when O 2 was present.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of O 2 activation by Cu(II) could involve Cu(I), as reported elsewhere. 46 Regarding Co-catalysts, upon O 2 addition most Co(II) complexes form kinetically inert lowspin Co(III) terminal superoxide or μ-peroxide compounds that are active only in catalysis by addition of a coreductant (often, an organic ligand with redox properties). 47 Hanna et al reported the oxidation of DMPO to the DMPO/ • OH adduct by Co(II) and ethylenediamine when O 2 was present.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogen on the hydroxyl group is detached and complexed with anions, and phenol is converted into a phenoxyl radical . Due to the instability of Cu­(I), it undergoes electron transfer with oxygen, activating molecular oxygen to generate the [O–O–Cu­(II)­HCl 4 ] 2– complex. , Because of the strong electronegativity of [O–O–Cu­(II)­HCl 4 ] 2– and the strong electron-withdrawing ability of the carbonyl group, the para position of the phenoxy radical shows strong electronegativity. Therefore, [O–O–Cu­(II)­HCl 4 ] 2– preferentially attacks the para position of the phenoxy group, generating p -benzoquinone and water.…”
Section: Resultsmentioning
confidence: 99%
“…48 The reactions were made in water and ethanol, respectively, with CCA-H and CCA-Li, although CCA-Li performs well in water. The choice aims at inhibit Li + /H + exchange that would be enhanced in H 2 O.…”
Section: Synthetic Approachmentioning
confidence: 99%